Laser eperiments for chemistry and physics - Motzkus, Marcus (Angewandte Chemie. International edition, 2016)
Oxford University Press, Oxford, 2015. 416 pp., softcover, £ 35.00.—ISBN 978-0198742982
Gesehen am 18.09.2020